The dark side of creativity: Coworker envy and ostracism as a response to employee creativity - Breidenthal, Amy P.; Liu, Dong; Bai, Yuntao; Mao, Yina (Organizational behavior and human decision processes, 2020)
•We extend the literature by studying interpersonal outcomes of creativity.•Relative creativity may result in coworker ostracism through coworker envy.•Relative CWX decreases the effect of relative creativity on coworker envy.•Relative LMX enhances the effect of relative creativity on coworker envy.•Time-lagged field studies provided support to our model. Globally, organizations are encouraging employees to be more creative in order to enhance organizational innovation. However, the potential negative coworker consequences stemming from employee creativity are widely unknown. Thus, we extend the creativity literature by drawing on social comparison theory and taking an interpersonal approach to investigate whether, when, and how employee relative creativity (an employee’s creativity compared to the average creativity in his or her team) may lead to coworker envy, which then results in coworkers ostracizing the focal employee. The findings reveal that coworker envy (Time 2) mediates the relationship between employee relative creativity (Time 1) and coworker ostracism (Time 3). When an employee has a relatively higher quality leader-member exchange relationship with his or her team leader (Time 1), his or her relative creativity (Time 1) is more likely to trigger coworker envy (Time 2) and ostracism (Time 3). In contrast, an employee’s relative creativity (Time 1) is more likely to fuel coworker envy (Time 2) and ostracism (Time 3) when he or she possesses relatively lower quality exchange relationships with coworkers (Time 1).